Eksplorasi Visual Cerita Rakyat Palembang “Legenda Pulau Kemaro” Dalam Karya Seni Digital - Simatupang, Putri Gracia; Budiaprilliana, Luh; Ruta, I Made (CITA KARA : JURNAL PENCIPTAAN DAN PENGKAJIAN SENI MURNI, 2024)
The report on the creation of the work entitled "Visual Exploration of Palembang Folklore, Legend of Kemaro Island" in Digital Art Works aims to introduce Palembang folklore so that it can be known by the wider community and encourage people to love the culture of their respective regions more. The process of creating digital works uses the Hawkins method, which includes exploration, experimentation and formation, and is equipped with a presentation method to display the results of the work. In the process of creating works, fine art elements such as points, lines, planes, shapes, spaces, colors, textures and light and darkness are applied and combined to create interesting visuals. This work is realized through non-proportional anatomical objects in the shape of children with fat and cute faces, inspired by the shape of bakpau. The choice of this shape provides visual uniqueness and an attractive impression. The results of the creation of this work are 16 (sixteen) digital works that visualize Palembang folklore, the Legend of Kemaro Island. These works were then presented as an interactive art installation with the title "A Story." Through this work, it is hoped that Palembang folklore can be better known and appreciated by the wider community, as well as encouraging a love of local culture. Thus, this work contributes to the preservation and introduction of regional culture to a wider generation, emphasizes telling stories that are rich in cultural values, and provides new experiences for art lovers.